2018
DOI: 10.1002/ep.13131
|View full text |Cite
|
Sign up to set email alerts
|

Iso‐conversional kinetic and thermodynamic studies of Indian sagwan sawdust pyrolysis for its bioenergy potential

Abstract: Thermochemical conversion of biomass for bio‐energy production is a potential option where condensable fractions can be utilized as fuel or for valuable chemicals and residual fractions for syngas (CO + H2) production. Present study aims at investigating the physicochemical properties and pyrolysis kinetics of Indian sagwan sawdust degradation using thermogravimetric analyzer at three heating rates (5, 10, and 20 K/min). Physical and chemical properties of ISS were determined by proximate, ultimate, compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The significant weight loss began only after 600°C, which revealed the decomposition of undegraded cellulose and lignin in ACTG 60 . The decrease in weight of ACTG after 647.46°C was due to rapid carbonization of the ACTG 9,67 …”
Section: Resultsmentioning
confidence: 99%
“…The significant weight loss began only after 600°C, which revealed the decomposition of undegraded cellulose and lignin in ACTG 60 . The decrease in weight of ACTG after 647.46°C was due to rapid carbonization of the ACTG 9,67 …”
Section: Resultsmentioning
confidence: 99%
“…The A increased with increasing SWH temperature for all residues (fresh and hydrolyzed). The lower values of A and E A denote an easier and faster decomposition of biomass at corresponding fractional conversion 59 . These values for fresh RS, fresh RH, HRS, and HRH are comparatively lower and can be treated thermochemically for bioenergy production.…”
Section: Resultsmentioning
confidence: 99%
“…Gupta and Mondal 59 investigated the physicochemical properties and pyrolysis kinetics of Indian sagwan sawdust degradation at three heating rates (5, 10, and 20°C min −1 ) and using isoconversional models of Flynn–Wall–Ozawa (FWO), Kissinger–Akahira–Sunose (KAS), and Friedman to calculate the activation energy. TG results showed that maximum devolatilization occurred at the temperature range of 207–477°C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The slow pyrolysis process, which operates at a relatively low temperature, heating rate, and high residence time, yields high amounts of solid product (between 40%-60%), whereas fast and flash pyrolysis yields high amounts of liquid product (biooil yield around 50%-80%) due to higher heating rate and very low residence time [10]. The solid by-product produced from pyrolysis is known as biochar which can be used as fertilizers, catalyst development (activated carbon synthesis), wastewater treatment, cosmetics, carbon-nanotubes, and bio-sorbents [11,12].…”
Section: Introductionmentioning
confidence: 99%